2020
DOI: 10.1080/13632469.2020.1802370
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Building Habitability after an Earthquake Using Building Typology and Damage Grade. Application in Lorca, Spain

Abstract: The present study proposes a statistical methodology to rate the habitability of different types of buildings after an earthquake. The first step was to rank variables that affect the vulnerability of a building and formúlate a statistical study with a discrimination Índex that makes it possible to identify buildings as habitable or non-habitable. This ranking applied the criteria established in various international guidelines that are used to distinguish between habitable (undamaged/no structural damage) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also, the response of the building is affected by the distance between the structure and the epicentre of the earthquake or the geology. Structure typology depends mainly on local building materials, climatic condition, the socioeconomic status, as well as the geology and geography factors [3]. In Guatemala City, it is very important to describe the earthquake, as it is not the same an interphase subduction earthquake than an in-slab subduction or a crustal zone (Benito et al 2012).…”
Section: Vulnerabilitymentioning
confidence: 99%
“…Also, the response of the building is affected by the distance between the structure and the epicentre of the earthquake or the geology. Structure typology depends mainly on local building materials, climatic condition, the socioeconomic status, as well as the geology and geography factors [3]. In Guatemala City, it is very important to describe the earthquake, as it is not the same an interphase subduction earthquake than an in-slab subduction or a crustal zone (Benito et al 2012).…”
Section: Vulnerabilitymentioning
confidence: 99%
“…This framework operates in near real time and encompasses three distinct levels of analysis: an empirical formulation, the effective stiffness concept, and the finite element model [11]. Martínez-Cuevas et al performed statistical modeling and found discrimination metrics based on various national criteria and a ranking of features to assess the habitability of houses after earthquakes [12].…”
Section: Introductionmentioning
confidence: 99%